Effect of flavonoids rutin and quercetin in peripheral neuropathy induced sensitive oxaliplatin - Maria Isabel Carneiro de Azevedo (2012)
Oxaliplatin is a third-generation platinum compound and the first-line treatment for colorectal cancer. The main limiting factor in oxaliplatin treatment is painful neuropathy that is difficult to treat. This side effect has been studied for several years, but its full mechanism is still inconclusive, and effective treatment does not exist. Data suggest that oxaliplatinâs initial neurotoxic effect is peripheral and oxidative stress-dependent. A spinal target is also suggested in its mechanism of action. The flavonoids rutin and quercetin have been described as cell-protecting agents because of their antioxidant, antinociceptive, and anti-inflammatory actions. We proposed a preventive effect of these agents on oxaliplatin-induced painful peripheral neuropathy based on their antioxidant properties. Methods: Oxaliplatin (1 mg/kg, i.v.) was injected in male Swiss mice, twice per week for 4 weeks. The development of sensory alterations, such as thermal allodynia and mechanical hypernociception, was evaluated using the tail immersion test in cold water (10ÂC) and the von Frey test. Rutin and quercetin (25-100 mg/kg, i.p.) were injected 30 min before each oxaliplatin injection. The animalsâ spinal cords were removed for histopathological and immunohistochemical evaluation and malondialdehyde and non-protein sulfhydryl group assays. Results: Oxaliplatin significantly reduced thermal and mechanical nociceptive thresholds, effects prevented by quercetin and rutin at all doses. Fos immunostaining in the dorsal horn of the spinal cord confirmed these results. The oxidative stress assays mainly showed that oxaliplatin induced peroxidation in the spinal cord and that rutin and quercetin decreased this effect. The flavonoids also decreased inducible nitric oxide synthase and nitrotyrosine immunostaining in the dorsal horn of the spinal cord. These results suggest that nitric oxide and peroxynitrite are also involved in the neurotoxic effect of oxaliplatin and that rutin and quercetin can inhibit their effect in the spinal cord. We also observed the preservation of dorsal horn structure using histopathological analyses. Conclusions: Oxaliplatin induced painful peripheral neuropathy in mice, an effect that was prevented by rutin and quercetin. The mechanism of action of oxaliplatin appears to be at least partially oxidative stress-induced damage in dorsal horn neurons, with the involvement of lipid peroxidation and protein nitrosylation.